Desporto federado, saúde e bem-estar subjetivo... Que relação?: Um estudo com adolescentes da Região Autónoma da Madeira - Mónica Micaela Andrade Camacho (2018)
The main objective of this study was to investigate the extent of which the federated sport practice is related to the Subjective Well-Being of teenagers of the Autonomous Region of Madeira, analyzing the differences according to the age and gender. The sample was formed by 641 teenagers with age between 11 and 24 years, which of 364 were males and 274 females, with an average age of 15.05 years (± 2.19). The Instruments used were the Inventory of behaviours, related to teenager's health, as well as the versions translated and adapted by the Office of Sports of Psychology and Satisfaction With Life Scale (SWLsp) as well as Positive and Negative Affect Schedule (PANAS-rd). The results showed that those who practiced sport more frequently were young people between the ages of 14 and 17, and that they had better levels of Life Satisfaction (LS) and Positive Affects (PA). It was also observed that males had a higher frequency of sports practice compared to females, as well as higher levels of LS and PA, which is why that young people who practice more times per week show higher levels subjective well-being. Also these are the ones that demonstrate a better perception of their own health. Therefore, we can conclude that in this sample, sports practice proved to be a good promoter of LS and PA and, as such, contributes positively to the BES of the teenagers as well to their perception of health. Palavras-Chave: Sports Practice; Subjective Well-Being; Health Perception; Satisfaction with life; Teenager.